PELATIHAN PUBLIKASI INSTANT WEBSITE DESA MENGGUNAKAN CHAT GPT DESA PANIMBANG, KECAMATAN CIMANGGU, KABUPATEN CILACAP - Aulia Shafira Tri Damayanti; Nandang Hermanto (Bajang Institute, 2023)
This journal is the result of community service in Panimbang Village, Cimanggu District, Cilacap Regency which aims to make instant publication of village websites using GPT Chat. The instant publication of the village website has the aim of increasing information accessibility and community participation in village development. The development method includes collecting village information needs, developing GPT Chat, and implementing village instant website publications. Evaluation is carried out through an assessment of community participation and accessibility of the information obtained. The results of this study are expected to provide real benefits for the people of Panimbang Village in obtaining the latest information and actively participating in village development.